Short Communication: Variation in chemical constituent of Styrax sumatrana wood growing at different cultivation site in North Sumatra, Indonesia - APRI HERI ISWANTO; YENNI SUHAIDA SIREGAR; ARIDA SUSILOWATI; ATMAWI DARWIS; RUDI HARTONO; BASUKI WIRJOSENTONO; HENTI HENDALASTUTI RACHMAT; ASEP HIDAYAT; WIDYA FATRIASARI (Biodiversitas Journal of Biological Diversity, 2019)
Iswanto AH, Siregar YS, Susilowati A, Darwis A, Hartono R, Wirjosentono B, Rachmat HH, Hidayat A, Fatriasari W. 2019. Variation in chemical constituent of Styrax sumatrana wood growing at different cultivation site in North Sumatra, Indonesia. Biodiversitas 20: 448-452. Kemenyan Toba (Styrax sumatrana) is known as endemic resin-producing trees that naturally grow in North Sumatra and distributed throughout five districts within the province. Different growing site may constitute to different characteristics of the species, e.g. morphological differences, chemical constituent, bioactive substances, etc. Different characteristics of wood chemical constituent are an important factor determining further utilization and potential use of wood in wider spectrums. Information about wood chemical constituent of Styrax sumatrana growing from different site has not been determined yet. Therefore, the objective of this research was to analyze the characteristics of chemical constituent of Styrax sumatrana wood originated from North Tapanuli and Pakpak Bharat according to axial direction of stem (bottom, middle, and top). Chemical properties such as hollocelulose, ?-cellulose, hemicellulose, Acid Soluble Lignin (ASL), acid insoluble lignin (AIL), and non-structural component (extractive content in ethanol benzene 1: 2 and ash content) were observed. Results showed that different growth location would yield in different wood chemical constituent. The wood chemical constituent from North Tapanuli and Pakpak Bharat were 52.72 and 69.80% (hollocelulose), 25.94 and 39.87% (?-cellulose), 26.78 and 29.92% (hemicellulose), 5.49 and 4.33% (Acid Soluble Lignin), 4.37 and 20.43% (Acid-Insoluble Lignin), 10.95 and 2.42% (extractive content), 1.37 and 0.8% for ash content.